Differentially expressed messenger RNA isoforms in beef cattle skeletal muscle with different fatty acid profiles - Salatta, Bruna Maria [UNESP]; Muniz, Maria Malane Magalhães [UNESP]; Fonseca, Larissa Fernanda Simielli [UNESP]; Mota, Lucio Flavio Macedo [UNESP]; Teixeira, Caio de Souza [UNESP]; Frezarim, Gabriela Bonfá [UNESP]; Serna-García, Marta [UNESP]; Arikawa, Leonardo Machestropa [UNESP]; Schmidt, Patrícia Iana [UNESP]; Nasner, Sindy Liliana Caivio [UNESP]; Silva, Danielly Beraldo dos Santos [UNESP]; Pereira, Angélica Simone Cravo; et al. (Elsevier, 2025)
This study aimed to identify mRNA isoforms that were expressed differently in the muscle tissue of Nellore cattle based on their intramuscular fatty acid profile. Forty-eight young bulls were used to quantify beef fatty acids (FA) and perform RNA sequencing analysis. The young bulls were divided into three different groups based on quantifying FA using k-means analysis. The Grp1 clustered animals with significantly elevated levels of PUFA, ω6, ω3, linoleic acid, α-linolenic acid, and PUFA/SFA ratios, indicating a more favorable fatty acid profile. Animals in Group 3 demonstrated significantly higher levels of palmitic acid, stearic acid, myristic acid, and SFA, which are less favorable fatty acid profiles. Grp2 included bulls with intermediate levels of fatty acids, positioned between the profiles of Grp1 and Grp3. Differential expression (DE) analyses were performed to compare these three distinct groups through the contrasts: Grp1 vs. Grp2, Grp1 vs. Grp3, and Grp2 vs. Grp3. The DE analyses identified a total of 62, 26, and 30 transcripts for the contrasts Grp1 vs. Grp2, Grp1 vs. Grp3, and Grp2 vs. Grp3, respectively. In the comparison between the Grp1 and Grp2 groups, we identified three mRNA isoforms, C7–203, ADD1–204, and OXT-201, which are involved in glycogen and lipid metabolism. These mRNA isoforms regulate the key genes responsible for fatty acid synthesis, leading to a higher PUFA content profile. On the other hand, in the comparison between the Grp1 and Grp3 groups, the mRNA isoforms RBM3–202 and TRAG1–202 were identified and play a crucial role in muscle development, adipogenesis, and concentration of PUFA and MUFA, respectively. The downregulation of THRSP-201 and FABP4–201, isoforms identified in both, Grp1 vs. Grp2 and Grp2 vs. Grp3, contrasts may contribute to lower levels of MUFA and SFA and higher levels of PUFA. In addition, these mRNA isoforms were associated with lipogenesis, fatty acid transport, and inhibition of lipolysis. Our findings suggest that the identified mRNA isoforms could serve as promising candidates to help develop strategies to select animals of higher nutritional meat quality.
Keywords: Beef cattle; Fatty acids; RNA-Seq; Transcriptome